Multi-Elemental Analysis of Crepis Sahendi Boiss Grown in Iraqi Kurdistan Region Using ICP-OES/ICP-MS Techniques - Osw, Peshawa Sh.; Masum, Pshtiwan A. (Science Journal of University of Zakho, 2017)
Crepis sahendi Boiss is perennial plant growing in Iraqi Kurdistan region. Traditionally, it is used for the treatment of abdominal ache. The objective of this study is to evaluate the element contents of root, stem, leaf and flower of C. sahendi, which were determined using microwave assisted digestion followed by ICP-OES/ICP-MS techniques. Sixty-five elements were analyzed from the studied plant parts. Element concentrations of Pt, Pd and Re have not been detected in any parts of the studied plant. Some elements were present only in specific parts, such as; Ta, Ti, U, Ho, Lu, Tm, Yb W, In and Te. The rest of the elements were detected in all parts of C. sahendi in different concentrations. Lead and Arsenic reach the toxic concentrations in flower with 45.9 ppm and 25.6 ppm respectively. Chromium was also showed in a toxic ratio within root, leaf and flower with 8.04 ppm, 7.43 ppm and 3.47 ppm respectively. The determination of metals as toxic ratio was depended on the WHO references. The presence of these toxic heavy metals in such a ratio in the selected parts of C. sahendi make us believe that this traditional plant is not safe to be used by consumers in the sampling area.
Keywords: The; A